Potential for Lung Recruitment and Ventilation-Perfusion Mismatch in Patients With the Acute Respiratory Distress Syndrome From Coronavirus Disease 2019*. Issue 8 (August 2020) - Mauri, Tommaso; Spinelli, Elena; Scotti, Eleonora; Colussi, Giulia; Basile, Maria Cristina; Crotti, Stefania; Tubiolo, Daniela; Tagliabue, Paola; Zanella, Alberto; Grasselli, Giacomo; Pesenti, Antonio
Abstract : Objectives: Severe cases of coronavirus disease 2019 develop the acute respiratory distress syndrome, requiring admission to the ICU. This study aimed to describe specific pathophysiological characteristics of acute respiratory distress syndrome from coronavirus disease 2019. Design: Prospective crossover physiologic study. Setting: ICU of a university-affiliated hospital from northern Italy dedicated to care of patients with confirmed diagnosis of coronavirus disease 2019. Patients: Ten intubated patients with acute respiratory distress syndrome and confirmed diagnosis of coronavirus disease 2019. Interventions: We performed a two-step positive end-expiratory pressure trial with change of 10 cm H2 O in random order. Measurements and Main Results: At each positive end-expiratory pressure level, we assessed arterial blood gases, respiratory mechanics, ventilation inhomogeneity, and potential for lung recruitment by electrical impedance tomography. Potential for lung recruitment was assessed by the recently described recruitment to inflation ratio. In a subgroup of seven paralyzed patients, we also measured ventilation-perfusion mismatch at lower positive end-expiratory pressure by electrical impedance tomography. At higher positive end-expiratory pressure, respiratory mechanics did not change significantly: compliance remained relatively high with low driving pressure. Oxygenation and ventilation inhomogeneity improved but arterial CO2 increased despite unchanged respiratory rate and tidal volume. The recruitment to inflation ratio presented median value higher than previously reported in acute respiratory distress syndrome patients but with large variability (median, 0.79 [0.53–1.08]; range, 0.16–1.40). The FIO2 needed to obtain viable oxygenation at lower positive end-expiratory pressure was significantly correlated with the recruitment to inflation ratio ( r = 0.603; p = 0.05). The ventilation-perfusion mismatch was elevated (median, 34% [32–45%] of lung units) and, in six out of seven patients, ventilated nonperfused units represented a much larger proportion than perfused nonventilated ones. Conclusions: In patients with acute respiratory distress syndrome from coronavirus disease 2019, potential for lung recruitment presents large variability, while elevated dead space fraction may be a specific pathophysiological trait. These findings may guide selection of personalized mechanical ventilation settings.